Utilization of Youtube as a Supplement of Mapping Skills Teaching Materials for High School Students in Banyuwangi District - M. Rizqon Al Musafiri (Journal of Multidisciplinary Science, 2022)
This research was conducted to improve the mapping skills of NU Genteng high school students using Youtube videos and combined with teacher-made geography modules. This study used a quasi-experimental design (quasi-experimental) which measured treatment through the pretest and post-test results. The treatment given is the same for students. As a result, students scored higher on the average post-test score compared to the pretest. This treatment affects students' academic achievement, especially in mapping skills in class XII social studies students. Youtube videos help students understand learning subjects more effectively.